Sosialisasi Pentingnya Bahan Pewarna Alam Untuk Benang Tenun di Desa Boti Kecamatan Kie Kabupaten Timor Tengah Selatan - Stevridan Yantus Neolaka (Jurnal Kelimutu Pengabdian Masyarakat, 2022)
Weaving is a work of Indonesian cultural heritage that has experienced development over time. As a form of answer to the above problems, the implementing team carried out outreach activities on the importance of natural dyes for woven yarn as well as providing training on dyeing techniques using naptol liquid for weaving craftsmen in Boti Village, providing dyeing technique training aimed at increasing knowledge about natural dyeing in the weaving process but still maintaining quality and quality of woven products. The implementation team will assist until partners can be independent. It is hoped that from this activity the weavers can increase their income level by selling quality woven products. The methods used in this activity are lectures, brainstorming and Focus Group Discussions (FGD). To understand the material, a discussion was formed accompanied by the facilitator. The implementation of this community service program (PKM) activity uses an anthropological and socialist approach, meaning that the approach in community service program activities (PKM) is carried out by means of kinship, kinship and humanism or an emic approach with the local community. This community service program (PKM) activity is incidental in nature, in the form of education for the community to strengthen people's understanding of the importance of natural dyes for weaving. This community service activity (PKM) was carried out on July 30, 2021. All material was well presented to participants according to the schedule. the facilitator or resource person delivers material in Indonesian and interspersed with local languages ​​so that it is easy for participants to understand and understand.